A description of the unknown female of Coleophora arenbergerella Baldizzone, 1985 (Lepidoptera: Coleophoridae) - Barton, Ian (Zootaxa, 2016)
During a trip to Cyprus, 27 September–4 October 2015, 4 specimens (3♂ and 1♀) of a Coleophora sp. unknown to the author were collected in the Oreites Forest, above Kouklia, Paphos District (N34 7307149: E32 6366901, altitude 340m). Two males and the one female were dissected. No match in habitus, or for the genitalia of either sex, was found when compared with any of the Coleophora sp. recorded for Cyprus (Fauna Europaea), other than C. arenbergerella about which no information could be found. The author contacted Giorgio Baldizzone, the author of the species, to see whether he could provide any information on C. arenbergerella; he kindly sent a copy of photos he had of the ♂ holotype, informing the author that the species was only known from that male. This allowed the author to confirm that the four specimens were C. arenbergerella, a species given as close to Coleophora kuehenella (Goeze) in Baldizzone (1985). So far this species is only known from Cyprus so may be endemic to the island.